Evaluation of Performance of Mutual Funds in India from 2004-2009 - Badani, Ankit (2009)
Mutual funds play an important role in the globalization of the financial markets. Various past studies have been carried out by academics and researchers to analyse the performance of mutual funds. One of the important facts revealed by most of these studies is that a mutual fund cannot perform better than the market. Performance measures like Sharpe ratio, Treynor ratio, Jensen measure etc are applied to evaluate the performance 30 open-ended equity diversified growth funds in India for the period April 2004 to March 2009. BSE-500 is selected as a benchmark in this study for comparison of the mutual funds. The empirical result in this study was in contrast with the previous studies conducted on performance of mutual funds. This study concludes that 50% of the funds selected in this study outperform the returns of the benchmark index (BSE-500).